Automatic image capturing system using air-transportation - Tsai Yew San (Universiti Malaysia Perlis, 2008)
The title of the project is Automatic Image Capturing System Using Air-Transportation. The objective of this project is to design RF communication system that will be able to link a camera with a computer wireless via microcontroller. The data of the image that the camera capture was send back to a PC ground station via the RF system. A camera was connected to the microcontroller and data was send to the microcontroller from the camera. Analog Digital Converter was used to enable the microcontroller to read the data since the camera data will be analog. RF link was use to enable communication between the computer and the microcontroller. Data was send to the computer and displayed in ASCII code form and binary form using Visual Basic using the RF link. Due to the project budget limitation, the air transportation is not used but instead the data that was transferred using RF system are considered as the successful simulation. The Number Plate Recognition project hopefully can be implemented into this project in the near future.